TYPICAL FEATURES OF INDIVIDUAL DWELLING LVIV AT THE END OF THE 19TH AND THE BEGINNING OF THE 20TH CENTURIES (TO THE MODERN PERIOD) - Березовецька, Ірина (SWorldJournal, 2024)
A large increase in the population led to an aggravation of the housing problem in the last third of the 19th century, which led to significant qualitative and quantitative changes in the field of housing construction. It was revealed that the following t